Part A: Write g(x) as a transformation of f(x).Part B: Write h(x) as a transformation of f(x).Part C: Write m(x) as a transformation of f(x)
![Part A Write gx as a transformation of fxPart B Write hx as a transformation of fxPart C Write mx as a transformation of fx class=](https://us-static.z-dn.net/files/d75/2bb74494e66975ce2860a2a6439d9c6d.png)
ANSWERS
• g(x) = f(x) - 2
,• h(x) = -f(x)
,• m(x) = f(x) + 7
EXPLANATION
The values on the table of function g(x) are all 2 less than the values of f(x). Therefore g(x) = f(x) - 2.
The values of function h(x) are all the opposite of the values of f(x). Therefore h(x) = -f(x).
The values of function m(x) are all 7 more than the values of f(x). Therefore m(x) = f(x) + 7.